Nachatki khristīanskago uchenīi͡a, ili, Kratkai͡a svi͡ashchennai͡a istorīi͡a i Kratkīĭ khristīanskīĭ katikhizis - Innokentiĭ, Saint, Metropolitan of Moscow and Kolomna, 1797-1879.; Net͡svi͡etov, Īakov. (Sanktpeterburg : Sinodalʹnai͡a tip., 1893)
Reprint of 1840 edition? Added t.p. in Aleutian, in Cyrillic characters. Russian and Aleut. Mode of access: Internet.